2022
DOI: 10.3390/cancers14246082
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment in Thymic Epithelial Tumors: A Narrative Review

Abstract: The tumor microenvironment (TME) is a complex and constantly changing entity. The TME consists of stromal cells, fibroblasts, endothelial cells, and innate and adaptive immune cells. Cancer development and progression occurs through this interplay between the tumor and the adjacent stroma. Cancer cells are capable of modifying their microenvironment by secreting various message-carrying molecules, such as cytokines, chemokines, and other factors. This action causes a reprogramming of the neighboring cells, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In recent times, there has been a shift in cancer treatment towards therapies that target molecules. Nevertheless, the rarity and histological heterogeneity of TET pose a challenge to new treatment development [ 42 ]. Individuals identified with TETs, irrespective of their particular histopathology, additionally exhibit an inexplicable tendency towards the emergence of autoimmune toxicity impacting the muscular or neuromuscular system [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent times, there has been a shift in cancer treatment towards therapies that target molecules. Nevertheless, the rarity and histological heterogeneity of TET pose a challenge to new treatment development [ 42 ]. Individuals identified with TETs, irrespective of their particular histopathology, additionally exhibit an inexplicable tendency towards the emergence of autoimmune toxicity impacting the muscular or neuromuscular system [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the development of immune toxicity has been associated with the response, as observed in other types of cancer ( 113 , 114 , 130 133 ).…”
Section: Role Of Immunotherapy In Thymic Tumors With or Without Co-mo...mentioning
confidence: 92%
“…In a very recent paper by Agrafiotis et al., the authors comprehensively reviewed the reliable data present in literature and summarized the current knowledge related to TME of TETs associated with a favorable or dismal prognosis ( 113 ). From these data, it was suggested that high expression of PD-L1 expression on tumor cells may be considered a marker of favorable prognosis, although this issue is controversial.…”
Section: Correlation Between Histotype and Tumor Microenvironment In ...mentioning
confidence: 99%
“…Other crucial tumor microenvironment components are tumor-associated macrophages (TAMs). TAMs are particularly enriched in TETs with higher TMB and in thymic carcinomas, where they are likely to exert pro-proliferative effects and facilitate tumor invasiveness [ 99 , 100 ]. TAMs within TETs express different heat shock proteins, such as HSP27 and HSP70, which contribute to tumor progression with their pro-inflammatory and anti-apoptotic functions.…”
Section: Molecular Pathologymentioning
confidence: 99%